The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1590/s1677-5538.ibju.2022.0521
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Ureterocalicostomy Technique

Abstract: Purpose: Ureterocalicostomy is a technique that was first described by Neuwirt in 1948 ( 1 ) The laparoscopic access was initiated in 2003 by Cherullo et al. ( 2 ), following the established principles of open surgery. In 2004, Gill et al. had two patients with UPJO treated with laparoscopic ureterocalicostomy, with success ( 3 ). In 2014, Arap et. al. presented a case series with good results in adults and children i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…A radionuclide scan conducted 1 year after the surgery indicated that the bilateral renal function levels were comparable, ultrasound showed no remaining hydronephrosis, and the urinary flow of the affected kidney was unobstructed [ 38 ]. In two case reports [ 16 , 34 ], both patients underwent UC due to obstruction of the ureteropelvic junction following pyeloplasty. The operation was successfully performed, and postoperative follow-up results demonstrated significant improvement in hydronephrosis with no evidence of anastomotic obstruction.…”
Section: Laparoscopic Ureterocalicostomymentioning
confidence: 99%
See 1 more Smart Citation
“…A radionuclide scan conducted 1 year after the surgery indicated that the bilateral renal function levels were comparable, ultrasound showed no remaining hydronephrosis, and the urinary flow of the affected kidney was unobstructed [ 38 ]. In two case reports [ 16 , 34 ], both patients underwent UC due to obstruction of the ureteropelvic junction following pyeloplasty. The operation was successfully performed, and postoperative follow-up results demonstrated significant improvement in hydronephrosis with no evidence of anastomotic obstruction.…”
Section: Laparoscopic Ureterocalicostomymentioning
confidence: 99%
“…However, with the continuous exploration of surgeons and the advancements in laparoscopic technology, laparoscopic or robot-assisted laparoscopic ureterocalicostomy (LUC or RALUC) has been increasingly performed on patients with severe hydronephrosis caused by complex upper ureteral stricture and obstruction. These procedures have shown satisfactory results [ 14 16 ]. A comprehensive search was performed using the PubMed database by entering the search term “ureterocalicostomy” to collect relevant studies on UC.…”
mentioning
confidence: 99%
“…They are to be congratulated on their significant contribution to the field, understanding that such cases should only be completed in the setting of a clinical trial and by highly skilled minimally invasive surgeons, with a low threshold for open conversion if adequacy of surgical resection is at all felt to be compromised. The second prize for best video of the year is awarded to Nunes, et al from the University of São Paulo for their submission entitled “Laparoscopic ureterocalicostomy technique” published in volume 49, number 3 of our journal ( 2 ). As we all know, reconstruction using an ureterocalicostomy is infrequently completed by even experienced urologists so this publication using a minimally invasive approach and marvelously captured and described represents an invaluable resource for urologists and trainees.…”
mentioning
confidence: 99%